1999
DOI: 10.1016/s0741-5214(99)70055-8
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of ureteroarterial fistula

Abstract: Ureteroarterial fistulas, although rare, appear to be increasing in frequency. Because open surgical repair may be difficult and associated with significant risk for complications, endovascular intervention may provide an attractive treatment alternative. We review the diagnosis and management of a ureteroarterial fistula and iliac pseudoaneurysm that presented with massive hematuria during ureteral stent removal. The patient was treated by means of the percutaneous embolization of the right hypogastric artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 11 publications
0
27
0
3
Order By: Relevance
“…Le pronostic des FAU s'est nettement amélioré ces der- nières années grâce aux progrès des techniques diagnostiques et thérapeutiques 6,7,23 . En effet, la mortalité en lien avec les FAU est passée de 70 % dans les années 80 à moins de 30 % 8 .…”
Section: Discussionunclassified
“…Le pronostic des FAU s'est nettement amélioré ces der- nières années grâce aux progrès des techniques diagnostiques et thérapeutiques 6,7,23 . En effet, la mortalité en lien avec les FAU est passée de 70 % dans les années 80 à moins de 30 % 8 .…”
Section: Discussionunclassified
“…[1][2][3][4][5][6][7][8][9] They have been reported to be associated with several conditions, including previous pelvic surgery, radiation therapy, indwelling ureteral stents, infection, primary vascular disease, and pregnancy. Among these etiologies, the fi rst three conditions appear to be the most important factors regarding the formation of such a fi stula.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several methods have been reported for treating ureteroarterial fi stulas. Recently, reports of interventional radiology methods have increased, including embolizing the artery 6 and a combination of embolizing the artery and surgical bypass grafting, 1,2,4,8 endovascular repair by stent-grafts, 3,5,9 and embolizing the ureter with nephrostomy. 7 Reports of endovascular treatment for the fi stulas by stent-grafts have increased since Kerns et al fi rst reported this treatment in 1996.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations